Dual-telescope multi-channel thermal-infrared radiometer for outer planet fly-by missions. (November 2016) - Aslam, Shahid; Amato, Michael; Bowles, Neil; Calcutt, Simon; Hewagama, Tilak; Howard, Joseph; Howett, Carly; Hsieh, Wen-Ting; Hurford, Terry; Hurley, Jane; Irwin, Patrick; Jennings, Donald E.; et al.
Abstract: The design of a versatile dual-telescope thermal-infrared radiometer spanning the spectral wavelength range 8–200 µm, in five spectral pass bands, for outer planet fly-by missions is described. The dual-telescope design switches between a narrow-field-of-view and a wide-field-of-view to provide optimal spatial resolution images within a range of spacecraft encounters to the target. The switchable dual-field-of-view system uses an optical configuration based on the axial rotation of a source-select mirror along the optical axis. The optical design, spectral performance, radiometric accuracy, and retrieval estimates of the instrument are discussed. This is followed by an assessment of the surface coverage performance at various spatial resolutions by using the planned NASA Europa Mission 13-F7 fly-by trajectories as a case study. Highlights: Dual-telescope thermal infrared radiometer for planetary exploration. Switchable wide-field-of-view and narrow-field-of-view telescope system. Measurement of thermal emission from cold planetary bodies. Determination of surface temperature and emissivity of icy moons. Determination of thermo-physical properties of icy planets and moons.